2015
DOI: 10.1016/j.chemosphere.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of perfluorinated alkylated substances in cereals, salt, sweets and fruit items collected in four European countries

Abstract: In the context of a European project, 12 perfluoroalkyl acids (PFAAs) were determined in 14 food items collected in four European countries representing northern, southern, eastern and western Europe. This study presents the results of PFAAs measured in fruit, cereals, sweets and salt. Out of the 12 PFAAs, 10 PFAAs were detected in 67% of the samples. Overall, PFOA was the most abundant compound and the highest concentrations were found for PFOS but all were less than 1ngg(-1). When comparing the four countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…D’Hollander et al reported that the range of PFAAs in cereals, salts, sweets and fruit items in four European countries was from ND to 1.09 ng·g −1 ·fw (10.9 ng·g −1 ·dw converted by 90% water content) [12], which was almost consistent with our study. The concentration range of PFAAs in vegetables from the four European countries showed a lower value (ND-1.31 ng·g −1 ·dw).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…D’Hollander et al reported that the range of PFAAs in cereals, salts, sweets and fruit items in four European countries was from ND to 1.09 ng·g −1 ·fw (10.9 ng·g −1 ·dw converted by 90% water content) [12], which was almost consistent with our study. The concentration range of PFAAs in vegetables from the four European countries showed a lower value (ND-1.31 ng·g −1 ·dw).…”
Section: Resultssupporting
confidence: 92%
“…The agricultural environment is polluted by PFAA perhaps due to the long range transport pathway, agricultural water irrigation and use of biosolids-amended soils [11]. Several field investigation papers have reported that PFAAs were widely detected in agricultural products (tea, cereals, salt, sweets, vegetables and fruit items) with PFOA showing a higher concentration [12,13,14,15]. Clark et al found the concentration of PFOA and PFOS in vegetables from the UK was up to 1000 pg·kg −1 ·ww.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rough estimate on PFOS intake through diet in Belgian adults by SES shows further that fish and fruit are major contributors to the total dietary PFOS intake (see Table 4; calculation based on food PFOS concentrations and food consumption (Table 3)). In the calculation shown in Table 4, assumed PFOS concentrations in foodstuffs were retrieved from the recent EU PERFOOD (PERFluorinated Organics in Our Diet) project [69], and were set equal to 0.003 ng/g for vegetables [70], 0.043 ng/g for meat [71], 0.061 ng/g for eggs [71], 0.098 ng/g for fruit [72] (mean of positive detects), 0.301 ng/g for freshwater/marine fish [71], and 0.523 ng/g for seafood [71]. The consumption of fish versus seafood was set at a ratio of 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts were implemented in 2006 to drastically reduce emissions of PFOA and its precursors by 95 % by 2010 and to work towards eliminating emissions and product content by 2015 [ 12 ]. Exposures to humans mainly occur through diet [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%